APLIKASI FORMULA PENILAIAN OPSI BLACK-SCHOLES UNTUK ESTIMASI NILAI CALL OPSI INDEKS SAHAM LQ-45 DI BURSA EFEK JAKARTA - Baruno, Agung; Sembel, Roy H. M. (Jurnal Akuntansi dan Keuangan Indonesia, 2004)
The objective of this research is to investigate the applicability of the Black-Scholes Option Pricing Model (BSOPM) on options on market index at the Jakarta Stock Exchange (JSX). A simulation is conducted using actual JSX LQ-45 index data between January 1997 and April 1999. Each month, a simulated premium of a one-month call option is calculated based on BSOPM and then compared with its payoff at its maturity date. The results show that the average profit of the simulated long stock index call option is negative but not statistically significant. It means that the BSOPM, although not rejectabie statistically, cannot be applied blindly on the valuation of JSX stock index options.